IN VITRO DEVELOPMENT OF Ascaridia galli EGGS INTO INFECTIVE EGGS AND LARVAE OF STADIUM 2 (L2) - Mubarokah, Wida Wahidah; Kurniasih, Kurniasih; Nurcahyo, Wisnu; Prastowo, Joko (Jurnal Kedokteran Hewan, 2019)
The study aimed at finding out the development of Ascaridia galli (A. gall) eggs that were given aerator treatment and those without aerator treatment into infective eggs and L2 through in vitro culture. Each treatments has 108,000 eggs assigned to 8 groups of 1,000; 2,000; 3,000; 4,000; 5,000; 6,000; 7,000; and 8,000 eggs, respectively with 3 repetitions. Female A. galli were collected from the small intestinal lumen of naturally infected domestic chickens. The eggs collected from the uterus of adult female A. galli were incubated in sterile aquadest at ambient temperature for 45 days (without aerator) and 25 days (with aerator) to obtain the infective eggs and the L2. The number of the infective eggs and hatched L2 were counted under stereo microscope. Data were analysed descriptively. There were 97.740 eggs (90.5%) in the groups without aerator developed into infective eggs and 77,040 eggs (71.3%) developed into the L2. Meanwhile, there were 101,847 eggs (94.3%) in the groups with the aerator developed into the infective eggs and88.722 eggs (82.15%) hatched L2. It is concluded that the eggs collected from worms uterus had high viability and the aerator application shortened the developing period of the A. galli worms.